Natural Sources of Volatile Organic Compounds to the Summer Arctic Troposphere - Mungall, Emma Louise (2018)
Due to chemistry-climate coupling, observations of chemical processes in the atmosphere are crucial to improving understanding of the Earth system and enabling future climate predictions. Quantifying the effect on climate of current and future anthropogenic influence requires first understanding natural processes. This task is complicated by the interactions between natural and anthropogenic emissions. Because the summer Arctic experiences limited anthropogenic influence, it is considered an analog for some pre-industrial atmospheres. Due to its remoteness, observations in the region are scarce. The goals of this thesis were to 1) make observations of the tropospheric composition of the summer Canadian Arctic Archipelago and 2) improve understanding of the sources of volatile organic compounds (VOCs) in the region. To achieve the first goal, two new datasets were collected by field deployment of chemical ionization mass spectrometers. The second goal was addressed through analysis of the newly collected data sets, modeling experiments, and laboratory experiments. This work confirmed that local marine sources are the major contributors to high levels of dimethyl sulfide (DMS) in the summer Arctic, and supported the hypothesis that DMS emissions from melt ponds on top of the sea ice may be significant. Unexpectedly, we found that heterogeneous chemistry at the sea surface microlayer emits large quantities of formic acid to the atmosphere, as well as smaller amounts of many other OVOCs, some of which may play a role in the formation of secondary organic aerosol. Methane sulfonic acid in aerosol particles, which has traditionally been considered a conservative tracer for DMS, was shown to be degraded by heterogeneous oxidation during atmospheric transport. Finally, the presence of high levels of formic and acetic acids in the summer Arctic calls into question the current understanding of the sources of these acids. In summary, this thesis begins to paint a clearer picture of the chemical composition of the summer Arctic troposphere while emphasizing that further measurements are badly needed to bring that picture into focus. Ph.D.